Prevalence of neoplasia diagnosed in dogs at the veterinary hospital at eduardo mondlane university, mozambique - Santos, I. F C [UNESP]; Cardoso, J. M M; Oliveira, K. C.; Laisse, C. J M; Bessa, S. A T (FapUNIFESP (SciELO), 2013)
A retrospective study of tumors in dogs was carried out in the School Veterinary Hospital (HVE), Eduardo Mondlane University, Mozambique, between January 2004 and January 2009. Data from clinical-surgical records of tumor samples surgically removed, necropsy and cytological exams were used and sent for histopathology exams. During the study 210 tumors and about 27 different types of tumors were identified. Skin tumors (61.0%) were the most frequent, followed by mammary gland tumors (27.60%), reproductive system tumors (11.90%) and bone system tumors. The mammary gland tumors were observed only in females, with high prevalence in bitches which were not spayed or spayed after two years old. It was concluded that the neoplasia prevalence increase was correlated to the higher longevity of dogs, and breed also contributed for the development of determined tumors due to high incidence of mastocitomas in Boxer and German Shepherd breeds. The 100 % incidence of mammary gland neoplasia in females confirmed the higher predisposition for mammary gland neoplasia in females.
Keywords: Dog; Histopathology; Mozambique; Neoplasia